Ternary natural deep eutectic solvent (NADES) infused phthaloyl starch as cost efficient quasi-solid gel polymer electrolyte - Selvanathan, V.; Azzahari, A.D.; Halim, A.A.A.; Yahya, R. (Elsevier, 2017)
A first-of-its-kind, eco-friendly quasi-solid bioelectrolyte derived from potato starch was prepared. Starch was chemically modified via phthaloylation to synthesize amorphous, hydrophobic starch derivative and the attachment of the phthaloyl group was confirmed via FTIR which showed phthalate ester peak at 1715 cm(-1); and H-1 NMR peaks between 7.30-7.90 ppm attributed to the aromatic protons of the phthaloyl group. The resulting starch derivative was then infused with ternary natural deep eutectic solvent (NADES) made from different molar ratios of choline chloride, urea and glycerol. Electrochemical Impedance Spectroscopy (EIS) revealed that the highest ionic conductivity was obtained by the system consisting of NADES with choline chloride:urea:glycerol in molar ratios of 4:6:2, with a magnitude of 2.86 mS cm(-1), hence validating the prospects of the materials to be further experimented as an alternative electrolyte in various electrochemical devices.